Comparison of Recurrence of High Trans-Sphinteric Anal Fistula After Vaaft and Tight Setons in Military Hospital Rawalpindi - Akbar, Muhammad Haroon; Bashir, Umar; Shabbir, Hassan; Ans, Muhammad; Majeed, Farhan Ahmed; Abbasi, Shahzad Ahmed; Khan, Attayaba; Amjad, Muhammad Ammar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the recurrence rate in patients undergoing fistulectomy using tight setons with those using videoassisted anal fistula treatment (VAAFT). Study Design: Comparative prospective study. Place and Duration of Study: Department of General Surgery, MH Rawalpindi, Pakistan from May 2018 to Dec 2021. Methodology: We included 200 patients with high trans-sphincteric anal fistula (simple or complex) of age 18 to 60 years, having ASA I or II. Group- A comprised patients undergoing treatment with VAAFT, while Group- B included patients undergoing treatment with Tight Seton in conventional surgery. Patients were followed for three months after the procedure. Patients having a history of discharge around or in the vicinity of the previous external opening of the anal fistula were labelled as having a recurrence. Recurrence was confirmed on MRI Fistulogram. Results: The mean age of patients in Group-A was 42.10±8.26 years, and in Group-B was 42.17±7.91 years (p=0.95). There were 58 male patients in Group-A and 55 male patients in Group-B (p=0.67). The mean duration of the fistula was 5.30±1.64 months in Group-A and 5.22±1.61 months in Group-B (p=0.72). Recurrence was diagnosed in 24 patients in Group-B and only 06 patients in Group-A (p<0.001). Conclusion: Video-assisted anal fistula treatment (VAAFT) has a lower recurrence rate than Tight Setons in conventional surgery in treating high trans-sphinteric anal fistula.